2015
DOI: 10.1039/c4ta05288a
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilica/carbon composite spheres as anodes in Li-ion batteries with excellent cycle stability

Abstract: 10Because of high capacity, relatively low operation potentials, abundance and environmental 11 benevolence, silica presents a promising anode material for high-energy lithium-ion batteries. 12 In this work, to enhance the conductivity of silica and ensure robust connection between 13 silica particles and the host structure in the anode, nanosilica/carbon composite spheres have 14 been fabricated via the in-situ copolymerization of formaldehyde and resorcinol on the 15 surface of nanosilica particles, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…5 is the cycle voltammetry curves of the a-Si@SiO x /Cr/C and a-Si@SiO x /Cr. In the first cycle, the a-Si@SiO x /Cr/C presents two reduction peaks at about 1.3 V and 0.8 V. Our previous study has confirmed that the two peaks correspond to the decomposition of electrolyte and the formation of SEI film [32]. The former is attributed to the reduction or decomposition of FEC, while the latter comes from that of other solvents like VC and EC.…”
Section: Resultssupporting
confidence: 55%
“…5 is the cycle voltammetry curves of the a-Si@SiO x /Cr/C and a-Si@SiO x /Cr. In the first cycle, the a-Si@SiO x /Cr/C presents two reduction peaks at about 1.3 V and 0.8 V. Our previous study has confirmed that the two peaks correspond to the decomposition of electrolyte and the formation of SEI film [32]. The former is attributed to the reduction or decomposition of FEC, while the latter comes from that of other solvents like VC and EC.…”
Section: Resultssupporting
confidence: 55%
“…Finally, the voltage platform of lithium insertion for the SiO x -C/GNPs is higher than those of graphite, which contributes to avoiding the formation For the SiO x -C/GNPs, two broad reduction peaks at about 1.35 V and 0.70 V in the first cycle, which disappear from the second cycle, are associated with the electrolyte decomposition and the formation of the solid electrolyte interface (SEI) layer. The former corresponds to the decomposition of FEC, while the latter is ascribed to the decomposition of other solvents in the electrolyte [41]. Both contribute to the irreversible capacity of the first discharge process.…”
Section: Resultsmentioning
confidence: 98%
“…The peak at 1.46 V is associated with the electrolyte decomposition and the formation of the solid electrolyte interface (SEI) layer. 37 The broad peak at 0.34 V corresponds to the reduction reactions of SiO x , while the broad anodic peaks at 0.38 and 0.52 V correspond to the dealloying process of Li x Si and a part of Li 2 Si 2 O 5 , 38,39 attributing to the delithiation of Li x Si back to amorphous Si.…”
Section: Resultsmentioning
confidence: 99%